Implementation of Kanorayang Customary Sanctions Imposed on Village Credit Institution Treasurers Kedewatan Traditional Village Ubud District, Gianyar - Anak Agung Istri Agung; Anak Agung Mas Adi Trinaya Dewi (Journal of Sustainable Development Science, 2024)
Given the increasingly urgent need for capital for rural communities, the local government, especially the Bali Provincial Government, has begun to develop financial institutions in rural communities known as Village Credit Institutions (LPD). The formulation of the problem in this study is: How is the Process of Implementing Kanorayang Sanctions by the Kedewatan Traditional Village, Ubud District, Gianyar Regency related to the Misappropriation of Customer Funds of the Kedewatan Traditional Village, Ubud District, Gianyar Regency and What steps were taken by the Head of Kedewatan Traditional Village, Ubud District, Gianyar Regency after the Kanorayang Sanction Decision. The type of research used by the author is empirical legal research. The conclusion of this study is as follows: The process of implementing Kanorayang sanctions by the Kedewatan Traditional Village, Ubud District, Gianyar Regency related to the Misappropriation of Customer Funds from the Village Credit Institution (LPD) of the Kedewatan Traditional Village, Ubud District, Gianyar Regency, which began with the financial report of the Village Credit Institution (LPD) reporting that the funds of the Village Credit Institution (LPD) of the Kedewatan Traditional Village, Ubud District, Gianyar Regency that were deposited in the Gianyar BPD were around 10 billion, after being investigated, it turned out that I Nyoman Ribek Adiputra admitted to using the LPD funds personally. The steps taken by the Bendesa of the Kedewatan Traditional Village, Ubud District, Gianyar Regency, included conducting an internal audit by the LPD, found irregularities and providing solutions to the LPD treasurer but were not implemented and finally at the time of the marriage of his son, I Nyoman Ribek Adiputra, was not given customary facilities and the status of his house was confiscated.